Friction and wear of the middle trough in scraper conveyors. Issue 6 (27th July 2018) - Li, Junxia; Liang, Shaowei
Abstract : Purpose: The study of the friction law and wear characteristics of the middle trough material can better select the appropriate material for the scraper conveyor of fully mechanized working face and provide theoretical support for the wear-resistant treatment technology. Design/methodology/approach: This paper investigated friction and wear of the middle trough in a scraper conveyor under different media. Lignite, coking coal and anthracite were selected media, and middle trough wear was maximum for anthracite and minimum for lignite, with coking coal being intermediate. Findings: Wear increased linearly with increasing load nonlinearly with increasing sliding speed. Middle trough wear also increased with increasing media granularity up to approximately 0.4 mm (40 mesh), but had little effect beyond that. Originality/value: It can provide a reference for the scraper conveyor running resistance. At the same time, it has great social significance and economic benefits for the safe, green and efficient coal mine industrial adjustment, etc.